Effects of Radiation on Materials: 21st International Symposium 2004
DOI: 10.1520/stp11214s
|View full text |Cite
|
Sign up to set email alerts
|

Properties of 20 % Cold-Worked 316 Stainless Steel Irradiated at Low Dose Rate

Abstract: Abstract:To assess the effects of long-term, low-dose-rate neutron exposure, tensile, hardness, and fracture properties were measured and microstructural characterization performed on irradiated 20% cold-worked Type 316 stainless steel. Samples were prepared from reactor core components retrieved from the EBR-II reactor following final shutdown. Sample locations were chosen to cover a dose range of 1-56 dpa at temperatures from 371-390°C and dose rates from 0.8-3.3 x10 -7 dpa/s. Irradiation caused hardening, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Despite the high volume fraction of carbide in modeling, the bulk of experimental data show a steady state volume fraction in the order of 0.1%. The exception is the data of Allen et al [45], particularly the value at ~30 dpa, which shows a volume fraction of about 1.3% (all precipitate formation percentages are given as volume fractions in this work unless otherwise labeled). While we cannot presently be sure of the explanation of the differences in this data vs. other experiments, it is observed that the highest value is comparable to the values predicted by our model.…”
Section: Carbidesmentioning
confidence: 81%
See 4 more Smart Citations
“…Despite the high volume fraction of carbide in modeling, the bulk of experimental data show a steady state volume fraction in the order of 0.1%. The exception is the data of Allen et al [45], particularly the value at ~30 dpa, which shows a volume fraction of about 1.3% (all precipitate formation percentages are given as volume fractions in this work unless otherwise labeled). While we cannot presently be sure of the explanation of the differences in this data vs. other experiments, it is observed that the highest value is comparable to the values predicted by our model.…”
Section: Carbidesmentioning
confidence: 81%
“…The phase fraction study ( Figure 7) shows that FCC_A1 (austenite), Sigma, Laves, and M 23 C 6 are stable phases at temperatures around 300 °C. However, reported experimental data on precipitates in 316 SS under irradiation in the LWR temperature range (~ 300 °C) do not show Sigma and Laves phases [9,11,12,[43][44][45]. This fact suggests that Sigma and Laves are kinetically inhibited phases in 316 SS under LWR conditions.…”
Section: Thermodynamicsmentioning
confidence: 96%
See 3 more Smart Citations